SMALL BUSINESS EFFICIENCY AND ITS ASSESSMENT IN UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines the importance of the development of small business and entrepreneurship for the economic growth of the regions of the Republic of Uzbekistan, as well as the features of assessing the effectiveness of small business. Effectiveness is a measure of the success of entrepreneurship and small business, therefore the article examines the relationship between these criteria and the conditions for achieving success. The issues discussed in the article are relevant for the economy of our country, because the use of measures aimed at the development of entrepreneurship and small business is one of the most important elements of state regulation of socio-economic processes, a factor of strengthening the country's innovative development and social stability. Increasing the level of economic activity of entrepreneurs, small business development programs that serve their self-sufficiency are of particular importance.